Reassessment of species delimitation using nuclear markers in three lentic-breeding salamanders from the Chugoku District of Japan (Amphibia: Caudata: Hynobiidae) - Tomimori, Yusuke; Matsui, Masafumi; Okawa, Hiroshi; Nishikawa, Kanto; Tanabe, Shingo; Kamasaka, Ryo (Zootaxa, 2023)
Hynobius akiensis sensu lato has recently been split into three species based on short sequence analyses of cyt-b gene of mtDNA and without data of nuclear DNA, and strange sympatric distribution in some areas has been indicated in two species. We analyzed nuclear DNA marker (SNPs) and complete sequence of cyt-b in H. akiensis sensu lato to reassess species delimitation and genetic introgression among species. As a result, we found two lineages with discordant mitochondrial and nuclear DNA in some areas. Of H. akiensis sensu lato, each of the two contains the type locality of two species recently reported (H. sumidai and H. geiyoensis), and the use of these names has been previously advocated. However, their sympatric distribution was rejected based on nuclear DNA data, which we consider is more reliable than mtDNA. We thus clarify geographic boundary of these two species and revise the species delimitations.